CONTROLLING THE CONTROLLER: EXPRESSIONS AND LIMITS OF THE SANCTIONING POWER OF THE PUBLIC ADMINISTRATION IN THE CASE OF THE COMPTROLLER GENERAL OF THE REPUBLIC - Carbajal Fierro, Solange Marianella (2025)
This article presents a detailed analysis of the Ruling issued on July 24, 2024, corresponding to Case No. 0026-2021-PI/TC, which establishes the limits of the sanctioning authority of the Office of the Comptroller General of the Republic. The document examines the aspects and principles that must be considered when the regulator defines or structures conducts that constitute infractions in any matter. The objective of the article is to explore and highlight the delimitation of the sanctioning authority of public entities, with a special focus on the Office of the Comptroller General of the Republic (CGR). In addition, the regulatory framework for the creation of infringing conducts is evaluated.